Benefit sanctions, social citizenship and the economy. (May 2019) - Webster, David
Throughout the history of National Insurance in the UK, there has been relatively little emphasis on benefit conditions or sanctions (previously called disqualifications). The relevant academic literature has been correspondingly thin. But over the past three decades there has been a dramatic shift to increased conditionality in social security, accompanied by increased harshness in the penalties. This has started to spawn a substantial new literature. This review article considers three significant recent publications. Although written from different perspectives, they all conclude that the current UK sanctions system cannot be justified. The review article argues that more attention needs to be paid to the flaws in the economic case for conditionality. It concludes that effective reform of the system depends on a reassertion of the concepts of social citizenship which underlay the development of National Insurance in the 20th century.